(untitled) (American Journal of Islam and Society, 1994)
This volume surveys the complex roles Islamic ideologies play in the politics of the Muslim world. The authors are distinguished scholars in Islamic history, philosophy, and law as well as specialists in the sociology and politics of various Muslim countries. Despite their varied disciplinary backgrounds and the vastness of their subject, the book features a remarkable degree of interconnection and does not sacrifice the analytical specificity needed for each essay. The volume’s fourteen articles ate grouped into six broad categories: History of Islamic Political Theory and Practice. These essays offer two interpretive histories of the evolution and cutrent status of Islam’s role in the political sphere. Ira Lapidus argues that Islamic political theory has been governed by two paradigms, each grounded in a separate vision of the Islamic "golden age." The first paradigm is the "seamless" Islamic ethos, a holistic conception of law, politics, and personal morality that existed at M a d i i under the Prophet and his four immediate political successots. Even though this period lasted for barely four decades, it continues to serve as the vision of the Islamic ideal, especially for the recurrent revivalist movements and thinkes who have based their appeals upon this "first golden age." The second paradigm is chatactenzed by diffemtiated religious and secular institutions. Despite attempts by medieval jurists to maintain the theoretical church-state unity, Islamic Societies developed tacit and clearly articulated spheres of religious and secular authority. This made it possible for the early Islamic empires to absorb and then live with non-Islamic traditions and peoples (i.e., Persians and Turks). This "second golden age" is epitomized by the Ottoman Empire, which nxognized Islam as the "official" religion and whose ruler was accepted as the titular caliph. Nevertheless, the fusion of teligion and politics was never complete, as reflected in the emergence of distinctly "religious" institutions parallel to those of the state. Modem Muslim states, Lapidus argues, are proof of the triumph of the second over the first paradigm. "Modern states can be seen as an expression of the historical separation of state and Islam .... All hope of salvation has been concentrated in the nonstate realm, in the religio-civil community, and in personal piety" (p. 23). As a result, states are not viewed by their own people, by and large, as the bearers of their religious ...